A comparative study of misoprostol oral versus vaginal route for induction of labour - DebBarma, Apratim Mohan; Baidya, Jahar Lal; Ray, Debasis (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Induction of labour at term is a common obstetric intervention. Prostaglandin E2 has been the agent of choice for pre-induction of cervical ripening for several decades. In recent time, prostaglandin E1 analogue (misoprostol) is a preferred new agent for pre-induction cervical ripening and labour induction owing to inexpensive, stable in room temperature, administrable through several routes. The ideal dose, route, and frequency of administration of misoprostol are still under investigation. Methods: A double blind parallel group placebo control randomized clinical trial was done in the department of obstetrics and gynecology of Agartala Govt. Medical College among 130 pregnant women those required induction of labour. In this clinical trial, the women were allocated by lottery to receive oral misoprostol (25 μg) and vaginal placebo (same dosage) or vaginal misoprostol (25 μg) and oral placebo (same dosage. Both active and placebo drug (25 mcg) were repeated at 4 hours. interval till the parturient reached active labour (not exceeding 5 doses). Both primary (induction delivery interval) and secondary outcomes (failed induction, vaginal/caesarean delivery rate, maternal and foetal complications) were statistically analyzed. Results: The mean induction delivery interval (primary outcome) differences were insignificant among both groups (oral versus vaginal). Success rate of induction (56.9% versus 75.4%), mean dosage (misoprostol 90.5 mcg versus 96 mcg) requirement, maternal and foetal complications was indifferent among two groups. The rate of vaginal delivery (within 24 hours of induction) was significantly higher when misoprostol was used through vaginal route. Caesarean section rate trends to be higher when misoprostol was administered orally. Conclusions: Low dose of misoprostol (25 mcg) offer an additional statistically significant clinical advantage in successful vaginal delivery when used vaginally.